Magnetisation reversal in Ising ferromagnet by thermal and field gradients. Issue 10 (October 2018) - Datta, Ranajay; Acharyya, Muktish; Dhar, Abyaya
Abstract: We report the results of the magnetisation reversal in Ising ferromagnet having thermal and field gradients by Monte Carlo simulation. We have studied the distribution of reversal times for different values of thermal and field gradients and compared the results with those obtained for uniform temperature. The movement of the domain wall of distinct domains and the growth of roughness of domain wall have also been studied statistically. The role of competing thermal and field gradients, in the reversal mechanism, was also studied and a line of marginal competition was obtained.